2015
DOI: 10.1097/inf.0000000000000565
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Invasive Pneumococcal Disease in Taiwan Following a National Catch-up Program With the 13-Valent Pneumococcal Conjugate Vaccine

Abstract: The 13-valent PCV catch-up program was associated with a significant decrease in serotype 19A IPD incidence in 2013, primarily in children eligible for the 13-valent PCV immunization. Continued surveillance is necessary to assess the further impact of the national catch-up program on pediatric IPD epidemiology in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…This is compatible with other retrospective studies, which showed that Sp-HUS most commonly developed 7e9 days (usually 3e13 days) after the onset of IPD. 6 In our cases, the TA-positive group had a significantly longer duration of anemia. The positive group also had a higher rate of AKI, suggesting that stronger neuraminidase activity was responsible for injury in this group and thus prolonged the disease course and hospitalization.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This is compatible with other retrospective studies, which showed that Sp-HUS most commonly developed 7e9 days (usually 3e13 days) after the onset of IPD. 6 In our cases, the TA-positive group had a significantly longer duration of anemia. The positive group also had a higher rate of AKI, suggesting that stronger neuraminidase activity was responsible for injury in this group and thus prolonged the disease course and hospitalization.…”
Section: Discussionsupporting
confidence: 47%
“…4,5 In Taiwan, the annual incidence is 32 cases per 100,000 population, with the highest incidence in the 2e4 years age group. 6 S. pneumoniae-associated hemolytic uremic syndrome (Sp-HUS) is recognized as one of the severe complications in IPD patients, and it manifests as hemolytic anemia, acute kidney injury (AKI) and thrombocytopenia. 7 Thomsen-Friedenreich antigen (TA; Galb1-3GalNAc) exposure, due to pneumococcal neuraminidase activity, had been described as the core pathogenesis of Sp-HUS, and previous study also proved TA was a positive predictor for Sp-HUS.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of PCV, among the 21 studies assessing IPD among children, serotypes included in PCV accounted for >60% of the total serotypes in 11 reports. 6,11,12,14,[16][17][18][19][20][21][22] Serotype 19A was among the most commonly identified in all of the geographic regions included in this review. In addition, serotypes 1 and 14 were prominent in Europe and Latin America and serotypes 6B, 14 and 19F were important in Africa-East Mediterranean, demonstrating geographic variations in the prevalence of PCV serotypes among pediatric IPD cases.…”
Section: Discussionmentioning
confidence: 99%
“…IPD results in high global morbidity and mortality each year [ 2 ], but it is a vaccine-preventable disease [ 3 5 ]. Its incidence decreased after the introduction of a seven-valent pneumococcal conjugate vaccine (PCV7) in the private sector in Taiwan in October 2005 [ 6 , 7 ]. The estimated coverage rate of PCV7 vaccination was 5.7 % in 2006 and 45.5 % in 2010 among children <5 years of age.…”
Section: Introductionmentioning
confidence: 99%